Membaca Serat Gembring Baring Karya Raden Ronggo Prawirodirjo III: Sebuah Ikhtiar Pencarian Pemimpinan Idaman Rakyat - Akhlis Syamsal Qomar; Warto Warto; Akhmad Arif Musadad (Universitas Sebelas Maret, 2022)
The old manuscript is one of the cultural heritages of the Indonesian nation which is full of noble values. One of the old literary works that has the function of piwulang is Serat Serat Gembring Baring by Raden Rangga Prawiradirja III [Madiun Regent 1796-1810]. The purpose of this study is to describe the leadership concepts contained in the Serat Gembring Baring in order to answer one of the mistakes of our state management, namely, the leadership crisis so that we can find the criteria for an ideal leader and what the people want. The content analysis method is used to reveal the leadership concept contained in the fiber, while the approach used is a historical-descriptive approach. A good leader in Fiber Gembring Baring is a leader who has the following criteria: kaṅ nĕdya hulaḥ praja (seriously government the country), maḍĕp kawulannira (pay attention to the people), mantĕp maraṅ hadabbiṅ nagari (be loyal to the adab [rules] of the country).